Nomadisme de l’équipe en Europe, les techniciens baroudeurs - Bérénice Bonhomme (Mise au Point)
This article proposes to raise the issue of the circulation of creative collaborators from the point of view of several technicians who work in several European countries, while at the same time developing a large part of their activity on French productions.